Smallholder Farmers’ Readiness for Contributing to Crop Microtakaful Scheme - Fauzilah Salleh; Nor Mazlina Abu Bakar; Nur Salina Ismail; Norfadzilah Rashid; Wan Jemizan Wan Deraman (Indonesian Journal of Sustainability Accounting and Management, 2023)
The study intends to identify smallholder farmers’ readiness to participate in Crop Microtakaful Scheme. This protection is significant for smallholder farmers to provide sustainable economic growth and food security. To understand the necessity of having the scheme, a few key areas must be observed. An overview of the smallholder farmers in Malaysia is presented, focusing on their demographics, readiness to participate in the scheme, and affordable contributions. In addition, risks and perils in agriculture, including natural disasters, pests, and crop diseases, are also outlined. The role of agriculture insurance/takaful is also discussed, highlighting its many benefits to smallholder farmers. For this study, a survey is carried out among 275 smallholder farmers to gain information on their demographic profiles, farming activities, and willingness to contribute to the Crop Microtakaful Scheme. The information is vital in developing a suitable and well-accepted Crop Microtakaful Scheme, specifically among the smallholder farmers in Malaysia. Findings show that a large percentage of the smallholder farmers were ready to participate in a takaful scheme to protect their crop losses. Contributions vary greatly, with 54.2% of respondents willing to contribute an amount ranging from RM50.00 to RM149.00, while 33.9% of respondents are only willing to contribute an amount of less than RM50.00. The Crop Microtakaful Scheme can reduce the community’s dependence on the government with stakeholders’ involvement in contributing a certain sum as part of their corporate social responsibility initiative.